Radiotherapy in the Adjuvant and Advanced Setting of CSCC - Muto, Paolo; Pastore, Francesco (Dermatology Practical & Conceptual, 2021)
Introduction: The use of radiotherapy for cutaneous squamous cell carcinoma (CSCC) has solid historical roots. It is used with patients who are not suitable for surgery, patients with high-risk histological features in the adjuvant setting, and in palliative care.Objectives: The aim of this article is to summarize and provide a radiation therapy overview on the indications, effectiveness, and potential adverse events of radiotherapy in the adjuvant and advanced setting of CSCC.Methods: We performed a comprehensive literature review on PubMed, adopted as our biomedical literature database. Articles were selected based on their date of publication (in the last 30 years) and relevance. Results: Radiotherapy (RT) can safely be used to manage non-surgical patients and high-risk patients in the advanced CSCC setting. The remarkable progress of delivery techniques has greatly improved the effectiveness and toxicity profile of RT treatments. From 2D techniques to intensity modulated radiation therapy (IMRT), and brachytherapy, all RT techniques have greatly advanced. To improve acute and chronic side effects, deeper care has been used. As regards CSCC, several dose fractionations and schedules have been suggested, in line with the patient’s age and medical conditions.Conclusions: RT is a fundamental and constantly evolving therapeutic option in the treatment of CSCC, to minimize the risk of recurrence and metastases in the adjuvant setting and in the exclusive treatment for non-surgical patients. Patients’ selection is crucial, together with and a collaborative team working approach among the specialists involved in disease management in the perspective of the best multidisciplinary assessment.